The methyltransferase METTL9 mediates pervasive 1-methylhistidine modification in mammalian proteomes - Erna Davydova (Nature Portfolio, 2021)
Only very few enzymes are known to catalyze protein histidine methylation. Here, the authors show that METTL9 is responsible for most 1-methylhistidine modifications in mouse and human proteomes, and characterize METTL9′s substrate specificity and potential cellular functions.